Population diversity of rice bacterial leaf blight isolates in Uganda - Habarurema, Innocent; Edema, Richard; Gibson, Paul; Lamo, Jimmy; Asea, Godfrey; Séré, Yacouba; Gasore, Elie R. (Asian Journal of Plant Science and Research, 2013)
The deployment of resistant cultivars is the best option to control bacterial leaf blight (BLB) and requires an understanding of the pathogen diversity. BLB caused by Xanthomonas oryzae pv.oryzae is a destructive disease of rice (Oryza sativa L.) in Uganda. Unfortunately, detailed information on Ugandan pathogen populations is not available. A set of 21 differential rice genotypes that have known resistance genes were used in a split plot design to test for differential virulence of six different isolates of X.oryzae pv.oryzae obtained from seed samples collected from Eastern Uganda. Statistical analysis showed diversity among isolates. The susceptibility of the differentials with two to four-gene combinations and the resistance of IR24 to Ugandan isolates were unusual and, therefore suggested a different pattern between Asian and Ugandan isolates at pathological level. Although the isolates were fewer in number, attempts to classify them into pathogenic races gave rise to 6 different races, as each isolate caused a particular virulence pattern on the differentials. The six races formed two significantly different (p ≤ 0.05) groups of one race (UX041) and five races (UX051, UX00, UX050, UX058 and UX044). These races would be used in screening rice germplasm available and/or newly introduced to Uganda.
Keywords: BLB; Isolate; NILs; Rice; Xanthomonas oryzae pv. oryzae